2005
DOI: 10.1097/01.tp.0000159142.62535.37
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Stable Mixed Chimerism by Embryonic Stem Cells Requires Functional Fas/FasL Engagement

Abstract: These data suggest a critical role for Fas-FasL engagement in ESC engraftment. We conclude that ESC may induce clonal deletion of alloreactive T cells by Fas-induced apoptosis in recipient T cells, protecting them from rejection. The data provide a rationale for improved protocols for the achievement of robust ESC-induced mixed chimerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…However, Koch et al [2007] demonstrated that ES cells suppress T cell proliferation in a contact-independent manner by secreting TGF-␤ . The mechanism proposed to mediate contact-dependent suppression of T cells is the induction of clonal deletion of alloreactive T cells by Fas-mediated apoptosis triggered by FasL expressed on ES cells [Fabricius et al, 2005]. However, 2 other reports provide evidence against this mechanism in murine ES cells [Brunlid et al, 2007;Koch et al, 2007].…”
Section: Susceptibility Of Es Cells and Their Derivatives To Lysis Bymentioning
confidence: 95%
See 3 more Smart Citations
“…However, Koch et al [2007] demonstrated that ES cells suppress T cell proliferation in a contact-independent manner by secreting TGF-␤ . The mechanism proposed to mediate contact-dependent suppression of T cells is the induction of clonal deletion of alloreactive T cells by Fas-mediated apoptosis triggered by FasL expressed on ES cells [Fabricius et al, 2005]. However, 2 other reports provide evidence against this mechanism in murine ES cells [Brunlid et al, 2007;Koch et al, 2007].…”
Section: Susceptibility Of Es Cells and Their Derivatives To Lysis Bymentioning
confidence: 95%
“…Lysis of murine ES cells was mediated in this case most likely by the combination of 2 factors: very low expression on ES cells of NK cell inhibitory MHC class I molecules and high expression of retinoic acid early inducible-1 (Rae-1) family of proteins, which serve as high-affinity ligands for the NK cell-activating receptor NKG2D [Bonde and Zavazava, 2006]. Similarly, in vitro generated alloreactive CTLs were not cytolytic against unstimulated murine ES cells, but were able to slightly lyse only the IFN-␥ -treated ES cells [Fabricius et al, 2005;Bonde and Zavazava, 2006]. In our hands, LCM virus-infected or peptide-loaded murine ES cells and their early differentiated progeny (embryoid body-derived cells on days 5 and 8 of differentiation) were also resistant to killing by activated LCM virusspecific syngeneic CTLs [Abdullah et al, 2007].…”
Section: Susceptibility Of Es Cells and Their Derivatives To Lysis Bymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, rat or mouse ES-derived hematopoietic cells can survive engraftment in a xenogenic or fully mismatched environment without immunosuppression. 55,66,67 This property may be due to the embryonic nature of ESCs, and seems to be conserved in hESCs. Li et al 68 have shown that hESCs and their derivatives can evade both in vivo xenogenic and in vitro allogeneic immune responses despite normal levels of MHCI.…”
Section: Rejection Of Allogenic Hescsmentioning
confidence: 99%